Malaysian dentists’ self-reported experience towards continuing clinical activity during the COVID-19 pandemic - Shani Ann Mani,; Nor Azlida Mohd Nor,; Jacob John,; Sabri Musa, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study assessed the self-reported symptoms/signs and precautionary measures towards continuing clinical practice during the second wave of the COVID-19 pandemic among Malaysian dentists. An online questionnaire was administered using Google Form distributed via social networks, email lists and social media pages to Malaysian dentists in both private and government sectors. Respondents were required to report their clinical activity during the three phases of the various Movement Control Order (MCO) imposed by the Malaysian government: namely the MCO, Conditional-MCO and the Recovery-MCO. Data was analysed with SPSS using descriptive and Chi-square tests. A total of 1548 dentists completed the survey. Five dentists reported being tested positive for COVID-19 test while 48 had one/more symptoms related to the disease. The majority perceived a real risk of COVID-19 transmission to dentists and more than 80% limited their clinical services to emergency/selective care during the MCO and C-MCO. About 17% of the dentists suspended face-to-face clinical activities during the MCO period but this figure dropped to 3.4% during the R-MCO. Clinical activities were limited mainly due to closure of workplaces (88.6%). Precautionary measures adopted at dental clinics included recording body temperature (54.2%), physical distancing in waiting rooms (84.6%) and hand washing prior to and after dental procedures (77.5%). The findings demonstrate that most dentists limited their clinical services during the MCO and resumed work once restrictions were lifted during the C-MCO and R-MCO. Many reported adopting appropriate precautionary measures to mitigate the spread of COVID-19.